DNA Methylation and RNA-DNA Hybrids Regulate the Single-Molecule Localization of a DNA Methyltransferase on the Bacterial Nucleoid - Nicolas L. Fernandez; Ziyuan Chen; David E. H. Fuller; Lieke A. van Gijtenbeek; Taylor M. Nye; Julie S. Biteen; Lyle A. Simmons (mBio, 2023)
ABSTRACT Bacterial DNA methyltransferases (MTases) function in restriction modification systems, cell cycle control, and the regulation of gene expression. DnmA is a recently described DNA MTase that forms N6-methyladenosine at nonpalindromic 5′-GACGAG-3′ sites in Bacillus subtilis, yet how DnmA activity is regulated is unknown. To address DnmA regulation, we tested substrate binding in vitro and found that DnmA binds poorly to methylated DNA and to an RNA-DNA hybrid with the DNA recognition sequence. Further, DnmA variants with amino acid substitutions that disrupt cognate sequence recognition or catalysis also bind poorly to DNA. Using superresolution fluorescence microscopy and single-molecule tracking of DnmA-PAmCherry, we characterized the subcellular DnmA diffusion and detected its preferential localization to the replisome region and the nucleoid. Under conditions where the chromosome is highly methylated, upon RNA-DNA hybrid accumulation, or with a DnmA variant with severely limited DNA binding activity, DnmA is excluded from the nucleoid, demonstrating that prior methylation or accumulation of RNA-DNA hybrids regulates the association of DnmA with the chromosome in vivo. Furthermore, despite the high percentage of methylated recognition sites and the proximity to putative endonuclease genes conserved across bacterial species, we find that DnmA fails to protect B. subtilis against phage predation, suggesting that DnmA is functionally an orphan MTase involved in regulating gene expression. Our work explores the regulation of a bacterial DNA MTase and identifies prior methylation and RNA-DNA hybrids as regulators of MTase localization. These MTase regulatory features could be common across biology. IMPORTANCE DNA methyltransferases (MTases) influence gene expression, cell cycle control, and host defense through DNA modification. Predicted MTases are pervasive across bacterial genomes, but the vast majority remain uncharacterized. Here, we show that in the soil microorganism Bacillus subtilis, the DNA MTase dnmA and neighboring genes are remnants of a phage defense system that no longer protects against phage predation. This result suggests that portions of the bacterial methylome may originate from inactive restriction modification systems that have maintained methylation activity. Analysis of DnmA movement in vivo shows that active DnmA localizes in the nucleoid, suggesting that DnmA can search for recognition sequences throughout the nucleoid region with some preference for the replisome. Our results further show that prior DNA methylation and RNA-DNA hybrids regulate DnmA dynamics and nucleoid localization, providing new insight into how DNA methylation is coordinated within the cellular environment.